Exploring the knowledge and attitudes of women of reproductive age from the general public towards egg donation and egg sharing: a UK-based study. Issue 8 (6th July 2021) - Bracewell-Milnes, Timothy; Holland, James C; Jones, Benjamin P; Saso, Srdjan; Almeida, Paula; Maclaran, Kate; Norman-Taylor, Julian; Nikolaou, Dimitrios; Shah, Nishel M; Johnson, Mark; Thum, Meen-Yau
Abstract: STUDY QUESTION: What are the knowledge and views of UK-based women towards egg donation (ED) and egg sharing (ES)? SUMMARY ANSWER: Lacking knowledge of the practices of ED and ES could be an influential factor in donor egg shortages, rather than negative perceptions or lack of donor anonymity and financial incentives. WHAT IS KNOWN ALREADY: The increasing age of women trying to conceive has led to donor egg shortages, with ED and ES failing to meet demand. Indeed, in recent years in the UK, ES numbers have fallen. This results in long waiting lists, forcing patients abroad for fertility treatment to take up cross border reproductive care. Previous research suggests a lack of knowledge of ED among members of the general public; however, no study has yet assessed knowledge or views of ES in the general public. STUDY DESIGN, SIZE, DURATION: Six hundred and thirty-five UK-based women over 18 years were voluntarily recruited from social media community groups by convenience sampling. The recruitment period was from February to April 2020. PARTICIPANTS/MATERIALS, SETTING, METHODS: Participants completed a previously validated questionnaire regarding female fertility, ED and ES, including knowledge, perceptions and approval of the practices and relevant legislation. This included ranking key benefits and issues regarding egg sharing. The questionnaire was completed using the online Qualtrics survey software. Statistical analysis was conducted using SPSS. MAIN RESULTS AND THE ROLE OF CHANCE: Regarding knowledge of ED and ES, 56.3% and 79.8%, respectively had little or no prior knowledge. Upon explanation, most approved of ED (85.8%) and ES (70.4%). A greater proportion of respondents would donate to a family member/friend (49.75%) than to an anonymous recipient (35.80%). Overall, ES was viewed less favourably than ED, with ethical and practical concerns highlighted. Women aged 18–30 years were significantly more likely to approve of egg donation practice compared to those aged >30 years ( P < 0.0001). Those against ES found fears of financial coercion or negative psychological wellbeing the most concerning. About 35.8% and 49.7% would personally consider anonymous and known ED, respectively, whilst 56.7% would consider ES. Those answering in favour of egg sharing were significantly more likely to give higher benefit ratings compared to those against the practice ( P < 0.001). Most agreed (55.8%) with and were not deterred to donate (60.1%) by the 'Disclosure of Donor Identity' legislation. Only 31.6% agreed with the compensatory cap; however, 52.7% would not be more motivated to donate by an increased cap. LIMITATIONS, REASONS FOR CAUTION: There were several limitations of the study, including the use of convenience sampling and the voluntary nature of participation opening the study up to sampling and participation bias. Finally, closed questions were predominantly used to allow the generation of quantitative data and statistical analysis. However, this approach prevented opinion justification and qualitative analysis, limiting the depth of conclusions drawn. WIDER IMPLICATIONS OF THE FINDINGS: To our knowledge, this is the first study to survey the general public's knowledge and views of ED/ES using a previously validated questionnaire. The conclusion that lack of knowledge could be contributing to the current donor shortfall in the UK demonstrates that campaigns to inform women of the practices are necessary to alleviate donor oocyte shortages. STUDY FUNDING/COMPETING INTEREST(S): No external funds were used for this study. The authors have no conflicts of interest. TRIAL REGISTRATION NUMBER: NA.